S100A11 (calgizzarin) is released via NETosis in rheumatoid arthritis (RA) and stimulates IL-6 and TNF secretion by neutrophils - Navrátilová, Adéla; Bečvář, Viktor; Baloun, Jiří; Damgaard, Dres; Nielsen, Claus Henrik; Veigl, David; Pavelka, Karel; Vencovský, Jiří; Šenolt, Ladislav; Andrés Cerezo, Lucie (Scientific reports, 2021)
S100A11 (calgizzarin), a member of S100 family, is associated with several autoimmune diseases, including rheumatoid arthritis (RA). Neutrophil extracellular traps (NETs) are implicated in the pathogenesis of RA and in the externalization of some S100 family members. Therefore, we aimed to determine the association between S100A11 and NETs in RA. For this purpose, the levels of S100A11 and NETosis markers were detected in the RA synovial fluid by immunoassays. The expression of S100A11 by neutrophils in the RA synovial tissue was assessed. Neutrophils isolated from peripheral blood were exposed to S100A11 or stimulated to release NETs. The levels of NETosis- and inflammation-associated proteins were analysed by immunoassays. NETs were visualized by immunofluorescence. We showed that S100A11 was expressed by the neutrophils in the RA synovial tissue. Moreover, S100A11 in the RA synovial fluid correlated with several NETosis markers. In vitro, S100A11 was abundantly released by neutrophils undergoing NETosis compared to untreated cells (p < 0.001). Extracellular S100A11 increased the secretion of IL-6 (p < 0.05) and TNF (p < 0.05) by neutrophils but did not induce NETosis. This study demonstrates, for the first time, that the release of S100A11 is dependent on NETosis and that extracellular S100A11 augments the inflammatory response by inducing pro-inflammatory cytokines in neutrophils.
Keywords: dospělí; extracelulární pasti; Arthritis, Rheumatoid; Female; revmatoidní artritida; Adult; Tumor Necrosis Factor-alpha; ženské pohlaví; S100 Proteins; lidé; synoviální tekutina; Interleukin-6; TNF-alfa; Extracellular Traps; Male; Aged; Neutrophils; interleukin-6; neutrofily; proteiny S100; lidé středního věku; Synovial Fluid; senioři; mužské pohlaví; Middle Aged; Humans